MODERN SERVER-SIDE RENDERING: A TECHNICAL DEEP DIVE - Nikhil Sripathi Rao (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Server-side rendering (SSR) has emerged as a pivotal architectural pattern in modern web development, bridging traditional server rendering with contemporary JavaScript frameworks. This article explores the evolution and implementation of SSR in current web applications, examining its impact on performance, search engine optimization, and user experience. It investigates the fundamental concepts underlying SSR, including isomorphic JavaScript architecture, hydration processes, and advanced rendering strategies. Through an examination of leading frameworks like Next.js and Nuxt.js, this article delves into practical implementation considerations and technical challenges. It encompasses critical aspects such as state management, caching strategies, and performance optimization techniques while highlighting the importance of proper resource utilization in SSR deployments. By examining real-world implementations across various scales, from small businesses to enterprise-level applications, this article provides insights into SSR's role in modern web architecture and its significance in building performant, accessible, and SEO-friendly applications.